Bioethical prescriptions to create, end, choose, and improve lives - Kamm, F. M. (Oxford ethics series, 2013)
'Bioethical Prescriptions' collects F.M. Kamm's articles on bioethics, which have appeared over the last twenty-five years and which have made her among the most influential philosophers in this area. Kamm is known for her intricate, sophisticated and painstaking philosophical analyses of moral problems generally and of bioethical issues in particular. This volume showcases these articles - revised to eliminate redundancies - as parts of a coherent whole